Effect of Food Waste on The Growth Performance, Waste Reduction Efficiency and Nutritional Composition of Black Soldier Fly (Hermetia illucens (L.), Diptera: Stratiomyidae) Larvae - Hariri, Muhammad Nur; Ishak, Ahmad Razali; Md Rashid, Razi Ikhwan (Malaysian Applied Biology, 2024)
The rate of solid waste generation, especially in Malaysia, has become one of the major concerns for environmental and public health issues. Food waste accounts for the highest percentage of solid waste that ends up in landfills. Due to the living nature of humans and their involvement in agricultural, industrial, and municipal activities, the disposal of food waste happens on a regular basis. Due to the absence of an incineration plant, these wastes are commonly sent into landfills which are considered to be the most cost-effective method for disposal. Nevertheless, consideration for an alternative disposal method such as composting shall not be ruled out entirely. One of the established methods for composting food waste is the utilization of the larvae of the Black Soldier Fly. A study was conducted to assess the growth and nutritional composition, waste reduction capacity and nutritional composition of Black Soldier Fly Larvae (BSFL) reared on food waste. We found that the larvae reared with the food waste and effective microorganism (EM), LFWEM (BSFL reared with a mixture of food waste and effective microorganisms), have a slightly better relative growth rate (2.66 ± 0.35 day-1) compared to larvae reared with only food waste (2.44 ± 0.17 day-1). The waste reduction index was higher in the LFWEM group (5.36 ± 0.18 g/day) compared to the control group, LFC (BSFL reared with chicken feed) (4.85 ± 0.03 g/day) and the LFW (BSFL reared with food waste) group (5.13 ± 0.17 g/day). The nutritional composition of the BSFL reared using food waste shows some potential as it surpasses some of the amount of essential amino acids including Arginine, Histidine, Threonine and Valine, found in the commercially available animal feeds. This finding serves as a baseline to propose potential replacements for animal protein by using BSFL reared with food waste.